2017
DOI: 10.1007/s10936-017-9502-2
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Contextual and Syntactic Information in the Processing of Turkish Anaphors

Abstract: In contrast with languages where anaphors can be classified into pronouns and reflexives, Turkish has a tripartite system that consists of the anaphors o, kendi, and kendisi. The syntactic literature on these anaphors has proposed that whereas o behaves like a pronoun and kendi behaves like a reflexive, kendisi has a more flexible behavior and it can function as both a pronoun and a reflexive. Using acceptability judgments and a self-paced reading task, we examined how Turkish anaphors are processed in isolate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…Further, they showed a complementary profile with reflexives, by dispreferring extra-sentential antecedents and preferring local and long-distance antecedents for kendisi and, to a lower extent, kendi as well. This finding is consistent with previous findings with Turkish monolinguals, which showed that kendi and kendisi both admit local and long-distance antecedents (Gračanin-Yuksek et al, 2017; Özbek and Kahraman, 2016). However, in contrast with the study by Gračanin-Yuksek et al (2017), heritage speakers were also more likely to select long-distance antecedents with kendisi than with kendi , showing some distinction between these anaphors.…”
Section: Methodssupporting
confidence: 93%
See 3 more Smart Citations
“…Further, they showed a complementary profile with reflexives, by dispreferring extra-sentential antecedents and preferring local and long-distance antecedents for kendisi and, to a lower extent, kendi as well. This finding is consistent with previous findings with Turkish monolinguals, which showed that kendi and kendisi both admit local and long-distance antecedents (Gračanin-Yuksek et al, 2017; Özbek and Kahraman, 2016). However, in contrast with the study by Gračanin-Yuksek et al (2017), heritage speakers were also more likely to select long-distance antecedents with kendisi than with kendi , showing some distinction between these anaphors.…”
Section: Methodssupporting
confidence: 93%
“…As in Gračanin-Yuksek et al (2017), the regions of interest consisted of the embedded verb and following regions. Note that due to Turkish word order, the verb region was the first point where participants could assess the compatibility between the target sentence and the preceding context (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the exact nature of kendi 'self' and its syntactic distribution are still controversial in Turkish syntax-semantics and syntax-discourse interface. The reader may have a look at Gracanin-Yuksek et. al.…”
Section: Quantificational Expressions and Appositivesmentioning
confidence: 99%